Conserved crosstalk between histone deacetylation and H3K79 methylation generates DOT1L‐dose dependency in HDAC1‐deficient thymic lymphoma. (17th June 2019) - Vlaming, Hanneke; McLean, Chelsea M; Korthout, Tessy; Alemdehy, Mir Farshid; Hendriks, Sjoerd; Lancini, Cesare; Palit, Sander; Klarenbeek, Sjoerd; Kwesi‐Maliepaard, Eliza Mari; Molenaar, Thom M; Hoekman, Liesbeth; Schmidlin, Thierry T; et al.
Abstract: DOT1L methylates histone H3K79 and is aberrantly regulated in MLL‐rearranged leukemia. Inhibitors have been developed to target DOT1L activity in leukemia, but cellular mechanisms that regulate DOT1L are still poorly understood. We have identified the histone deacetylase Rpd3 as a negative regulator of budding yeast Dot1. At its target genes, the transcriptional repressor Rpd3 restricts H3K79 methylation, explaining the absence of H3K79me3 at a subset of genes in the yeast genome. Similar to the crosstalk in yeast, inactivation of the murine Rpd3 homolog HDAC1 in thymocytes led to an increase in H3K79 methylation. Thymic lymphomas that arise upon genetic deletion of Hdac1 retained the increased H3K79 methylation and were sensitive to reduced DOT1L dosage. Furthermore, cell lines derived from Hdac1 Δ/Δ thymic lymphomas were sensitive to a DOT1L inhibitor, which induced apoptosis. In summary, we identified an evolutionarily conserved crosstalk between HDAC1 and DOT1L with impact in murine thymic lymphoma development. Synopsis: Identification of a conserved chromatin crosstalk, in which histone deacetylases Rpd3/HDAC1 restrict H3K79 methylation, uncovers a DOT1L‐dose dependency of thymic lymphoma in HDAC1‐deficient mice. Yeast histone deacetylase and transcriptional repressor Rpd3 restricts Dot1‐mediated histone H3K79 methylation at its target genes. The murine Rpd3 homolog HDAC1 negatively regulates DOT1L‐mediated H3K79 methylation in thymocytes. Murine thymic lymphomas caused by the loss of HDAC1 depend on proper DOT1L dosage. Abstract : Rpd3/HDAC1 histone deacetylases restrict Dot1‐mediated H3K79 methylation in yeast and mammals, with consequences for murine lymphomagenesis.